Simplifying the Expression: (x+y)(2x+y)+(x+2y)(x-y)
This problem involves expanding and simplifying an algebraic expression. Let's break it down step by step:
Step 1: Expanding the Expressions
We can expand the expressions using the FOIL method (First, Outer, Inner, Last).
-
(x+y)(2x+y):
- First: x * 2x = 2x²
- Outer: x * y = xy
- Inner: y * 2x = 2xy
- Last: y * y = y²
- Combined: 2x² + xy + 2xy + y² = 2x² + 3xy + y²
-
(x+2y)(x-y):
- First: x * x = x²
- Outer: x * -y = -xy
- Inner: 2y * x = 2xy
- Last: 2y * -y = -2y²
- Combined: x² - xy + 2xy - 2y² = x² + xy - 2y²
Step 2: Combining Like Terms
Now, we have: (2x² + 3xy + y²) + (x² + xy - 2y²)
Combining the terms with the same variables and exponents:
- x² terms: 2x² + x² = 3x²
- xy terms: 3xy + xy = 4xy
- y² terms: y² - 2y² = -y²
Step 3: The Final Solution
Putting it all together, the simplified expression is:
(x+y)(2x+y)+(x+2y)(x-y) = 3x² + 4xy - y²